Pengaruh Pengetahuan Alat Pelindung Diri Terhadap Tingkat Kecelakaan Kerja Konstruksi Menggunakan Metode Rank Spearman - Ade Rizki Nurmayadi; Septi Putri Sandi Ratih (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
Knowledge of personal protective equipment is the most basic thing that must be understood by construction workers. Low knowledge makes workers ignorant and negligent of the importance of personal protective equipment while working. This will increase the risk of work accidents that will affect work productivity. This study aims to determine the relationship between the level of knowledge about personal protective equipment against construction work accidents in Yogyakarta. The method used in this study is a quantitative study by observing construction work accidents. This research was conducted by taking data directly from the field (questionnaire) which was then analyzed using the Rank Spearman correlation test method, to determine the relationship between the level of knowledge about Personal Protective Equipment. The population is 52 a sample of sample of 30 respondents. From this data, then analyzed the relationship between workers' knowledge of personal protective equipment and work accidents using Spearman rank correlation. The results showed calculated value of 0.760 and when compared with the Spearman rank correlation coefficient table (Rho), the arithmetic value bigger table was 0.361 at a significance level of 0.05. This value is in the ranges from 0.70 to 0.89 which states that the relationship was very strong. The results can be used as a basis in improving the condition and exsisting construction management, so that work accidents can be minimized.